ANALISIS PERBANDINGAN PENGGUNAAN HEDGINGANTARA FORWARD CONTRACT DENGAN CURRENCY SWAP UNTUK MEMINIMASI RISIKO FOREIGN EXCHANGE - Ni Wayan Eka Mitariani; IB Panji Sedana; Ida Bagus Badjra (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2013)
This study aims is to identifying the differences between using forward contract hedging or currencyswap hedging. Paired Sample T-Test were used to answer the problems and to test the hypothesis. The findings showthat without paying attention to the time value of money, currency swap hedging generated higher income value than forward contract hedging, whereas by paying attention to the time value of money, forwardcontracthedging generated higher income value than currency swap hedging. Significant differences were foundas far as the use of forward contract hedging and currency swap hedging are concerned, both by paying or noattention to the time value of money.